Response to language barriers with patients from refugee background in general practice in Australia: findings from the OPTIMISE study - Shoko Saito; Mark F Harris; Katrina M Long; Virginia Lewis; Sue Casey; William Hogg; I-Hao Cheng; Jenny Advocat; Geraldine Marsh; Nilakshi Gunatillaka; Grant Russell (BMC, 2021)
Abstract Background Language is a barrier to many patients from refugee backgrounds accessing and receiving quality primary health care. This paper examines the way general practices address these barriers and how this changed following a practice facilitation intervention. Methods The OPTIMISE study was a stepped wedge cluster randomised trial set within 31 general practices in three urban regions in Australia with high refugee settlement. It involved a practice facilitation intervention addressing interpreter engagement as one of four core intervention areas. This paper analysed quantitative and qualitative data from the practices and 55 general practitioners from these, collected at baseline and after 6 months during which only those assigned to the early group received the intervention. Results Many practices (71 %) had at least one GP who spoke a language spoken by recent humanitarian entrants. At baseline, 48 % of practices reported using the government funded Translating and Interpreting Service (TIS). The role of reception staff in assessing and recording the language and interpreter needs of patients was well defined. However, they lacked effective systems to share the information with clinicians. After the intervention, the number of practices using the TIS increased. However, family members and friends continued to be used to interpret with GPs reporting patients preferred this approach. The extra time required to arrange and use interpreting services remained a major barrier. Conclusions In this study a whole of practice facilitation intervention resulted in improvements in procedures for and engagement of interpreters. However, there were barriers such as the extra time required, and family members continued to be used. Based on these findings, further effort is needed to reduce the administrative burden and GP's opportunity cost needed to engage interpreters, to provide training for all staff on when and how to work with interpreters and discuss and respond to patient concerns about interpreting services.